Screening and Prognostic Value of Methylated Septin9 and its Association With Clinicopathological and Molecular Characteristics in Colorectal Cancer - Sun, Jie; Xu, Jinling; Sun, Chao; Zheng, Minying; Li, Yuwei; Zhu, Siwei; Zhang, Shiwu (Frontiers in Molecular Biosciences, 2021)
Screening of CRC continues to show poor compliance of endoscopy examination. The detection of mSEPT9 in peripheral blood is among the safe and simple early screening methods for CRC. The issue of how to elucidate whether detection of mSEPT9 in peripheral blood can effectively improve compliance of endoscopy and increase the early diagnosis rate of CRC and the relationship between levels of mSEPT9 in the peripheral blood and clinical stage, pathological classification, and expression of characteristic molecules in CRC remains unsolved. A total of 7759 individuals participated in the study that was performed using a questionnaire for screening of high-risk CRC. The endoscopic detection compliance of individuals with high-risk CRC who underwent the fecal occult blood test (FOBT) or mSEPT9 test was compared based on the results of the questionnaire. Additionally, correlation of mSEPT9 levels in the peripheral blood with clinicopathological features, mutation status of TP53, mismatch repair deficiency (dMMR), and KRAS/NRAS/BRAF/PIK3CA genotype was analyzed, and association of biomarkers with cancer-specific survival (CSS) and time to recurrence (TTR) was compared. We also detected levels of mSEPT9 in the peripheral blood of patients with CRC 7 days after surgery and compared the prognostic value of mSEPT9 with CEA. Results of our study showed that the mSEPT9 test could improve compliance of endoscopy and indicated a higher percentage of patients with positive mSEPT9 willing to undergo endoscopy detection than in those with positive FOBT. The specificity and sensitivity of mSEPT9 were better than that of FOBT for the detection of CRC. mSEPT9 was associated with the TNM stage, dMMR, and mutations in TP53, BRAF, and PIK3CA. A Ct value of mSEPT9 ≤ 37.5 was significantly related to poor CSS. mSEPT9 could affect association of dMMR and BRAF and PIK3CA mutations with CSS in a specific stage of CRC. The positive rate of mSEPT9 after surgery was found to correlate with poor TTR, and sensitivity was higher than CEA. The combination of mSEPT9 with CEA had a better prognostic value than that of mSEPT9 alone. The level of mSEPT9 was related to dMMR, mutations in TP53, BRAF, and PIK3CA, and was an effective biomarker for the prognosis of patients with CRC.